16. ASSOCIATED FACTORS WITH LOW BIRTH WEIGHT AT A HOSPITAL IN THAI NGUYEN (Vietnam Journal of Community Medicine, 2025)
Objectives: This study seeks to analysis of some factors related to low birth weight at Thai Nguyen Hospital A.Materials and Methods: Comparative cross-sectional descriptive study: Convenient sampling, selecting all medical records of children and their mothers at A hospital in Thai Nguyen during the study period, meeting the selection criteria. In fact, in 2023, we selected 306 medical records of women giving birth to low birth weight that met the criteria for selecting the research group. For 01 medical record that meets the criteria for inclusion in the research group, select 01 medical record with an adjacent medical record number that meets the criteria for selecting the comparison group. Thus, the sample size for the comparison group is 306.Results: Factors related to low birth weight include: women who are ethnic minorities (OR = 1.4; 95%CI 1.03 - 2.0), women who gain < 8 kg during pregnancy (OR = 3.0; 95%CI: 2.0 – 4.4), mothers with a history of low birth weight (OR = 2.6; 95%CI: 1.2 - 5.5); primipara (OR = 1.42; 95%CI: 1.03 - 1.95); had medical conditions during pregnancy (OR = 2.7; 95%CI: 1.7 - 4.3 ); anemia (OR = 1.1; 95%CI 1.1 – 3.5), women with preeclampsia (OR = 3.9; 95%CI 2,0 - 7.5); Our study did not find a relationship between maternal age and low birth weight infants.Conclusions: Factors associated with low birth weight include: women who are ethnic minorities, women who gain weight < 8 kg during pregnancy, women who are anemic, who give birth to a first child, women with medical conditions during pregnancy, women with preeclampsia, mothers with a history of low birth weight.
Keywords: Low birth weigh; associated factors; A Hospital